Repackaging Milton for the Late Seventeenth-Century Book Trade Jacob Tonson, Paradise Lost, and John Dryden's The State of Innocence - Depledge, Emma (Oxford: Oxford University Press, 2021)
This chapter focuses on the magisterial 1688 folio edition of Paradise Lost, published by Jacob Tonson and Richard Bentley, exploring the possible reasons why these men chose to publish Milton at this time, as well as the impact the edition had both on Milton’s authorial afterlife and on their careers as stationers. The chapter places the 1688 Paradise Lost folio in the wider context of Tonson’s career, including his involvement in pirate publication schemes and his status (from 1678) as Dryden’s publisher, to argue that the 1688 edition of Paradise Lost, one of the most profound turning points in Milton’s authorial afterlife, had less to do with the political context of 1688 and the perceived vendibility of the poem and more to do with Tonson’s own ambitions and frustrations as a stationer.
Keywords: Publication; Paradise Lost (1688); Jacob Tonson; book trade; John Dryden; The State of Innocence; illustrations; Richard Bentley; Subscription publication